Pollen morphology characterization of Dryades Groppo, Kallunki & Pirani, a new genus of Rutaceae, and its phylogenetically related species - Dutra, Fernanda Vitorete; Groppo, Milton; Gasparino, Eduardo Custódio [UNESP] (Taylor & Francis, 2023)
Rutaceae (Sapindales) is represented by approximately 2040 species and 150–170 genera. Conchocarpus is the genus with the highest number of species and is circumscribed by a combination of character states, making it a polymorphic group. A recent study proposed a new genus, Dryades, formed by species formerly positioned in Conchocarpus. This study aims to describe the pollen morphology of Dryades species, comparing it with the palynology of phylogenetically related species, to present data that can characterize the species of Dryades. We analyzed the pollen grains of Dryades species and eight species of the genera Andreadoxa, Angostura, Erythrochiton, Galipea, Rauia and Conchocarpus. The pollen grains were acetolyzed, measured, described qualitatively, and analyzed quantitatively. Illustrations using light microscopy (LM) and scanning electron microscopy (SEM) are presented. Multivariate analysis was performed. The pollen grains are monads, isopolar, medium to very large in size, with subcircular to subtriangular amb, and oblate-spheroidal to prolate shape. The apertures are 3- or 5-colporate, varying in size (very small to very large colpi). The endoapertures are usually lalongate, rarely circular. The pollen grains analyzed are microreticulate, reticulate, macroreticulate, reticulate-baculate, baculate or verrucate-baculate. Both qualitative and quantitative characteristics of pollen grains proved to be important in distinguishing genera and grouping species within genera (in particular, the number of apertures, the length of the ectoaperture, the exine ornamentation and the size of the pollen grains). Dryades species show similarities in pollen morphology to species of related genera such as Andreodoxa, Galipea and especially Rauia. The shape of pollen grains and the number of apertures in Dryades are distinct from those found in Conchocarpus macrophyllus. The pollen data observed in this study confirm the pollen diversity of Rutaceae.
Keywords: Galipeeae; Galipeinae; palynology; taxonomy